The Effect of Religiosity, Understanding of Taxation and Love of Money on Perceptions of Tax Evasion with Risk Preference as a Moderating Variable - Yessy Rusilawaty; Herman Ernandi (Journal of Islamic and Muhammadiyah Studies, 2023)
This study aims to determine the effect of religiosity, understanding of taxation and love of money on perceptions of tax evasion with risk preference as a moderating variable. Study on Accounting and Management Students at Muhammadiyah University of Sidoarjo. The analytical tool used is tabulation of the questionnaire, data collection in the form of validity and reliability tests. The hypothesis in this study is the influence of religiosity, understanding of taxation and love of money on perceptions of tax evasion with risk preference as a moderating variable. By testing the hypothesis using the SmartPLS analysis tool. The results obtained based on the validity test showed that all questions on the questionnaire were declared valid. To test the reliability of all variables the Composite Realibility value or Cronsbach's Alpha value is declared reliable. And for hypothesis testing based on R-Square and T-Statistic values, allphypothesesparepaccepted, the resultspstatepthat the influence of religiosity, understanding of taxation and love of money moderated by risk preference has an effect on perceptions of tax evasion.